2012
DOI: 10.1037/a0026739
|View full text |Cite
|
Sign up to set email alerts
|

Do other-reports of counterproductive work behavior provide an incremental contribution over self-reports? A meta-analytic comparison.

Abstract: Much of the recent research on counterproductive work behaviors (CWBs) has used multi-item self-report measures of CWB. Because of concerns over self-report measurement, there have been recent calls to collect ratings of employees' CWB from their supervisors or coworkers (i.e., other-raters) as alternatives or supplements to self-ratings. However, little is still known about the degree to which other-ratings of CWB capture unique and valid incremental variance beyond self-report CWB. The present meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
493
3
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 531 publications
(526 citation statements)
references
References 91 publications
25
493
3
5
Order By: Relevance
“…We speculate that undesirable private behaviors, such as CWB, delinquency, and unethical decisions, might be better predicted by self-reports than by observer reports because people are motivated to keep these actions, and proclivities toward these actions, hidden (Berry, Carpenter, & Barratt, 2012). Behaviors that are more public and less undesirable might be more amenable to prediction by observer reports (John & Robins, 1993;Vazire, 2010).…”
Section: Self-other Perceptions Of Moral Character 33mentioning
confidence: 99%
“…We speculate that undesirable private behaviors, such as CWB, delinquency, and unethical decisions, might be better predicted by self-reports than by observer reports because people are motivated to keep these actions, and proclivities toward these actions, hidden (Berry, Carpenter, & Barratt, 2012). Behaviors that are more public and less undesirable might be more amenable to prediction by observer reports (John & Robins, 1993;Vazire, 2010).…”
Section: Self-other Perceptions Of Moral Character 33mentioning
confidence: 99%
“…However, supervisor or co-worker reported knowledge hiding might not reflect knowledge hiding accurately because the definition of knowledge hiding involves concealment of information [18]. What is more, a recent meta-analysis conducted by Berry et al (2012) reveals that other-reported assessments of counterproductive work behaviour, such as knowledge hiding, do not capture unique and valid incremental variance beyond what self -reports capture and may even assess such behaviour more narrowly [33]. Future research could utilize experimental study to measure knowledge hiding more accurately.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Anchors ranged from 1 (strongly disagree) to 7 (strongly agree). We examined negative affectivity as a control variable given its potential influence on conceptually relevant endogenous variables (i.e., anxiety, anger, and CWBs; e.g., Berry, Carpenter, & Barratt, 2012;Burke, Brief, & George, 1993).…”
Section: Daily Problem Prevention Behaviors Were Assessed With Two Itmentioning
confidence: 99%